The role of international support programmes in global health security capacity building: A scoping review. - Anne Doble; Zoe Sheridan; Ahmed Razavi; Anne Wilson; Ebere Okereke (PLOS Global Public Health)
Large scale public health emergencies such as COVID-19 demonstrate the importance of Global Health Security (GHS) and highlight the necessity of resilient public health systems capable of preparing for, detecting, managing, and recovering from such emergencies. Many international programmes support low- and middle-income countries (LMICs) to strengthen public health capabilities for compliance with the International Health Regulations (IHR). This narrative review seeks to identify key characteristics and factors necessary for effective and sustainable IHR core capacity development, establishing roles for international support and some principles of good practice. We reflect on the "what" and the "how" of international support approaches, highlighting the importance of equitable partnerships and bi-directional learning, and inviting global introspection and re-framing of what capable and developed public health systems look like.